Urinary interleukin‐6 is a potentially useful diagnostic and prognostic marker of acute kidney injury in dogs. (27th August 2022) - Chen, Hilla; Avital, Yochai; Mazaki‐Tovi, Michal; Aroch, Itamar; Segev, Gilad
Abstract: Background: Interleukin‐6 (IL6) is a pro‐inflammatory cytokine implicated in the pathophysiology of urinary tract diseases. The objective of this study was to evaluate the diagnostic and prognostic utilities of urinary IL6 (uIL6) in dogs with acute kidney injury (AKI) and other urinary tract diseases. Methods: Eighty client‐owned dogs were included and divided into four groups: AKI, chronic kidney disease (CKD), urinary tract infection and healthy controls. Urine samples were analysed for uIL6 and normalised to urinary creatinine (uIL6/uCr). Results: Dogs in the AKI group had higher uIL6/uCr compared with the control and CKD groups ( p  < 0.001 and 0.012, respectively). Receiver operator characteristic (ROC) curve analysis of uIL6/uCr as a diagnostic marker for AKI had an area under the curve (AUC) of 0.91 (95% confidence interval [CI], 0.81–1.0) with 82% sensitivity and 90% specificity (cutoff point 4.5 pg/mg) when including the AKI and control groups. ROC analysis including AKI compared with all other groups had an AUC of 0.77 (95% CI, 0.67–0.87) for the diagnosis of AKI with sensitivity and specificity of 71% and 78%, respectively (cutoff point 10.4 pg/mg). The 30‐day mortality of the AKI group was 34%, and there was no difference in uIL6/uCr between survivors and non‐survivors of AKI. Conclusions: uIL6/uCr is a potentially sensitive and specific diagnostic marker for AKI in dogs.